2014
DOI: 10.1093/jxb/eru275
|View full text |Cite
|
Sign up to set email alerts
|

The 2-C-methylerythritol 4-phosphate pathway in melon is regulated by specialized isoforms for the first and last steps

Abstract: Highlight textThis research describes the role of specialized isoforms encoding regulated steps of the MEP pathway in melon and provides evidence for their functional specialization in seedling greening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 70 publications
1
32
0
Order By: Relevance
“…DXS1 is a limiting factor in upregulation of the carotenoid pathway in A. thaliana 49 . DXS1 expression is induced by light 50,51 , and it is the main DXS isoform catalyzing the biosynthesis of isoprenoid and carotenoid precursors in photosynthetic metabolism 52,53 . DXS1 also regulates carotenoid accumulation in A. thaliana and tomato 54,55 .…”
Section: A Model For Carotenoid Accumulation In Carrot Rootsmentioning
confidence: 99%
“…DXS1 is a limiting factor in upregulation of the carotenoid pathway in A. thaliana 49 . DXS1 expression is induced by light 50,51 , and it is the main DXS isoform catalyzing the biosynthesis of isoprenoid and carotenoid precursors in photosynthetic metabolism 52,53 . DXS1 also regulates carotenoid accumulation in A. thaliana and tomato 54,55 .…”
Section: A Model For Carotenoid Accumulation In Carrot Rootsmentioning
confidence: 99%
“…Moreover, specialized isoforms of DXS can also regulate the MEP pathway in melons (Saladie et al . ). Previous studies have shown that the overexpression of DXS results in elevated levels of carotenoids and other terpenoids (Estévez et al .…”
Section: Discussionmentioning
confidence: 97%
“…As a major controlling enzyme of the MEP pathway, the activity of DXS can be regulated by different mechanisms (Banerjee & Sharkey 2014) such as feedback inhibition by IDP and DMADP (the final metabolites of the MEP pathway) (Banerjee et al 2013) and feedforward regulation by GAP (a substrate of DXS) (Patel et al 2012). Moreover, specialized isoforms of DXS can also regulate the MEP pathway in melons (Saladie et al 2014). Previous studies have shown that the overexpression of DXS results in elevated levels of carotenoids and other terpenoids (Estévez et al 2001;Enfissi et al 2005).…”
Section: Hc-pro Promotes Plastidic Isoprenoids Biosynthesis 2031mentioning
confidence: 99%
See 2 more Smart Citations